FIXED POINT RESULTS IN QUASI CONE METRIC SPACE FOR GENERALIZED a - y CONTRACTIVE MAPPINGS USING DIAMETER OF ORBITS - Sila, Eriola Belul (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
E. Karapinar and B. Samet (2012) [1] have given some fixed point theorems related a - y Contractive Mappings in metric space. N. Bilgili, E. Karapinar and B. Samet (2014) [2] have proved these results in quasi metric space. In this paper we prove some new results for the existence and uniqueness of fixed point in quasi cone metric space using generalized a - y Contractive Mappings related with diameter of orbits.